Revolving vane compressor - Willy, Perdana Tanuwijaya (2013)
Efficiency is the most important factor affecting the performance of a compressor. Mainly, there are two types, i.e. mechanical and volumetric efficiency. The former is indicated by low frictional losses, while the latter by low leakage